1997
DOI: 10.1128/jvi.71.11.8672-8677.1997
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of interleukin-4 delays virus clearance in mice infected with respiratory syncytial virus

Abstract: Although interleukin-4 (IL-4) expression has been implicated in vaccine-enhanced respiratory syncytial virus (RSV) disease, its role in mediating the immune response to primary RSV infection remains unclear. To assess the effect of IL-4 production on typical RSV infection, transgenic mice which either overexpress or fail to express IL-4 were challenged intranasally with RSV and their responses were compared to those of the parent strains. IL-4-deficient mice eliminated virus from the lung as quickly as did C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…IL-4 has also been shown to influence the CTL response to RSV. Overexpression of IL-4 during RSV infection results in delayed virus clearance and enhanced illness, and is associated with abrogated CD8þ cytolytic T cell activity [10]. The effect on CD8 þ T cell function in this setting is related to altered cytolytic function, and does not alter frequency or IFN-g production in CD8 þ T cells [33,34].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…IL-4 has also been shown to influence the CTL response to RSV. Overexpression of IL-4 during RSV infection results in delayed virus clearance and enhanced illness, and is associated with abrogated CD8þ cytolytic T cell activity [10]. The effect on CD8 þ T cell function in this setting is related to altered cytolytic function, and does not alter frequency or IFN-g production in CD8 þ T cells [33,34].…”
Section: Discussionmentioning
confidence: 96%
“…IL-13 has many of the same immunomodulatory properties as IL-4, partly because both cytokines signal through the IL-4 receptor a-chain [5]. Previously, our group found that IL-4 significantly delayed RSV clearance which was associated with suppression of the development of virus-specific cytotoxic lymphocytes [10], suggesting that IL-13 might have a similar effect. However, IL-13 plays a more critical role in immunity to the gastrointestinal nematode Nippostrongylus brasiliensis and the intracellular parasite Leishmania major than IL-4 [11,12], highlighting divergent phenotypic effects of these cytokines in in vivo models of infection.…”
Section: Introductionmentioning
confidence: 93%
“…For example, we have previously shown that IL-2 suppresses, but IL-4 enhances, HSV-1 replication in the eye. 27,62,63 Detrimental effects on host animals were also observed in experiments in which IL-4 -expressing transgenic mice were infected with respiratory syncytial virus 64 and in which animals infected with influenza virus infection were treated with recombinant IL-4. 65 In addition, IL-4 expression by a recombinant vaccinia virus has been found to exacerbate infection.…”
Section: Discussionmentioning
confidence: 85%
“…35,36 The development of controlled-release mechanisms is crucial for translational applications and may avoid potential adverse effects of IL4. [37][38][39] The NFκB-IL4 MSC-based cell therapy significantly improved immunomodulation and minimized adverse effects. The crosstalk between MSCs and M2 macrophages could potentially further enhance bone regeneration.…”
Section: Discussionmentioning
confidence: 99%